George and Martha - Marshall, James, frey50; Houghton Mifflin Company (Boston, MA : Brilliance Corporation, 1987)
Five stories about two great friends.
Split pea soup -- The flying machine -- The tub -- The mirror -- The tooth.
Page turn signals on Side 1.
Ages 4-8.
70092
Keywords: Friendship -- Fiction -- Juvenile sound recordings; Hippopotamus -- Fiction -- Juvenile sound recordings